2016
DOI: 10.1111/ppa.12568
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene signalling is essential for the resistance of Nicotiana attenuata against Alternaria alternata and phytoalexin scopoletin biosynthesis

Abstract: The phytohormone ethylene plays an important role in plant defence responses to pathogen attack. When infected by the necrotrophic fungal pathogen Alternaria alternata (tobacco pathotype), which causes severe diseases in Nicotiana species, the wild tobacco plant Nicotiana attenuata accumulates a high amount of the jasmonate (JA)‐dependent phytoalexin scopoletin to defend itself against this fungal pathogen. However, it is still not known whether ethylene signalling is also involved in scopoletin biosynthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…In contrast to the observation in N. benthamiana inoculated with P. infestans , our experiments did not support the role of ethylene signaling in capsidiol elicitation in N. attenuata - A. alternata pathosystem. When NaEIN2 was silenced by VIGS, A. alternata -elicited NaF6’H1 was dramatically reduced, which is consistent with our previous finding that ethylene signaling is essential for scopoletin biosynthesis (Sun et al ., 2017), but NaEAH s and NaEAS s trancripts were induced to levels similar to plants transformed with empty vector (Supplementary Fig. S3).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to the observation in N. benthamiana inoculated with P. infestans , our experiments did not support the role of ethylene signaling in capsidiol elicitation in N. attenuata - A. alternata pathosystem. When NaEIN2 was silenced by VIGS, A. alternata -elicited NaF6’H1 was dramatically reduced, which is consistent with our previous finding that ethylene signaling is essential for scopoletin biosynthesis (Sun et al ., 2017), but NaEAH s and NaEAS s trancripts were induced to levels similar to plants transformed with empty vector (Supplementary Fig. S3).…”
Section: Discussionsupporting
confidence: 91%
“…Previously, we have demonstrated that, in response to A. alternata inoculation, N. attenuata plants activate both jasmonate and ethylene signaling pathways to regulate the biosynthesis of the phytoalexins scopoletin and its β-glycoside form, scopolin (Sun et al ., 2014b; Li and Wu, 2016; Sun et al ., 2017). As feruloyl-CoA 6’-hydroxylase 1 ( NaF6’H1 ), the key enzyme gene for scopoletin biosynthesis, was highly elicited at 1 day post inoculation (1 dpi) when the infection was at early stage and only a few of fungal hyphae had been observed to penetrate into leaf tissues via stomata (Sun et al ., 2014a), transcriptome analysis was performed in A. alternata -inoculated N. attenuata leaves at 1 dpi to identify secondary metabolites which could potentially act similarly to scopoletin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To monitor the progress of VIGS, we silenced phytoene desaturase ( PDS ), which causes plants to show visible bleaching of green tissues two to three weeks after transformation ( Saedler and Baldwin, 2004 , Wu et al., 2008 , Sun et al., 2017 ). When the leaves of PDS -silenced plants began to bleach, the source–sink transition leaves of EV and VIGS plants were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to cultivated tobacco, N. attenuata is attacked by A. alternata , a notorious necrotrophic fungus that causes brown spot disease in tobacco species in the field ( Schuck et al., 2014 ). In response to this fungal infection, N. attenuata plants activate abscisic acid (ABA)-mediated stomatal defense ( Sun et al., 2014a ), as well as the jasmonate (JA) and ethylene signaling pathways ( Sun et al., 2014b , Sun et al., 2017 , Li and Wu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%